Societal Threat to Safety, Compensatory Control, and Right‐Wing Authoritarianism. Issue 6 (6th June 2013) - Mirisola, Alberto; Roccato, Michele; Russo, Silvia; Spagna, Giulia; Vieno, Alessio
<x xml:space="preserve">Abstract</x> We analyzed directly and indirectly the relationships between societal threat to safety, perceived control, and the increase in right‐wing authoritarianism (RWA) in two studies. In Study 1 (national sample of the Italian population, N = 1, 169), we performed a longitudinal analysis structured into three waves (January 2003, September 2004, and January 2005). A moderated regression analysis showed that RWA increased from 2003 to 2005 as a function of perceived societal threat to safety more among low‐ than among high RWA scorers. In experimental Study 2 (Italian university students, N = 131) a moderated mediation model showed loss of perceived control to mediate the relation between societal threat to safety and the increase in RWA, but among low authoritarians only. Limitations, implications, and possible developments of this research are discussed.